Use Of Fermented Rubber seed (Havea bransiliesis) In The Diets Feeds On Growth Of Catfish (Pangasius pangasius) Fingerlings - Riga Oganda; Indra Suharman; Adelina ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
The research was conducted for 56 days from March to April 2015. The aim of this research was to find out respons of Catfish (Pangasius pangasius) fingerling on use of fermented is the diets. Four isonitrogenous (35% crude protein) experimental diets was formulated to contain 0, 20, 30, and 40% Fermented Rubber seed and 100, 80, 70, and 60% soybean meal (A, B, C, D, respectively). Completely randomized design (CRD) was used in this experimentThe result showed that a diet containing 40% Fermented Rubber seed and 60% soybean meal (D) support a good specific growth rate (3.03%/day), feed efficiency (31.63%,) and protein retention (26.31%.). Survival rate of fish was high (100%). It this concluded that up to 60% soybean meal can be substituted Fermented Rubber seed in the diets for freshwater catfishKey word: Diets, Fermented Rubber seed, Growth, Utilization, Pangasius pangasius